Make Room for Daddy : The Journey from Waiting Room to Birthing Room - Leavitt, Judith Walzer (Book collections on Project MUSE., 2009)
Using fathers' first-hand accounts from letters, journals, and personal interviews, along with hospital records and medical literature, this book offers a new perspective on the changing role of expectant fathers from the 1940s to the 1980s. It shows how, as men moved first from the hospital waiting room to the labour room in the 1960s, and then on to the delivery and birthing rooms in the 1970s and 1980s, they became progressively more involved in the birth experience and their influence over events expanded.